Stress hormones concentrations in the normal microenvironment predict risk for chemically induced cancer in rats - Valente, Vitor Bonetti [UNESP]; Verza, Flávia Alves [UNESP]; Lopes, Felipe Yudi Kabeya [UNESP]; Ferreira, Joana Zafalon [UNESP]; dos Santos, Paulo Sérgio Patto [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Soubhia, Ana Maria Pires [UNESP]; de Andrade, Mariza; de Oliveira, Sandra Helena Penha [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2018)
Evidence show that stress hormones can influence cancer progression, but its role in carcinogenesis is poorly understood. In this study, we used a new method based on oral carcinogenesis model in rats to test the hypothesis that physiological levels of stress hormones in the normal tissue microenvironment would have significant predictive value for chemically induced cancer occurrence. Male Wistar rats were submitted to a tongue biopsy for measuring not-stress induced levels of norepinephrine, corticosterone, adrenocorticotropic hormone (ACTH) and brain-derived neurotrophic factor (BDNF) in the tissue before carcinogenic induction. Rats were treated with the 4-nitroquinoline-1-oxide (4NQO) chemical carcinogen for twenty weeks and then euthanized for microscopic evaluation of the tongue lesions. Increased pre-carcinogen norepinephrine concentrations and reduced basal corticosterone levels in the normal tissue microenvironment were predictive for oral squamous cell carcinoma (OSCC) occurrence. Likewise, increased pre-carcinogen norepinephrine levels in the normal microenvironment were associated a lower expression of pCDKN2a-p16 in OSCCs. Post-carcinogen levels of corticosterone and BDNF in oral leukoplakia tissues (precursor lesion of OSCC) and post-carcinogen corticosterone concentrations in OSCCs were higher than basal levels in the normal mucosa. Increased norepinephrine concentrations in OSCCs were associated to a greater tumor volume and thickness. Furthermore, higher levels of norepinephrine, ACTH and BDNF in OSCCs were associated to a lesser intensity of the lymphoplasmocytic infiltrate. This study shows that pre-carcinogen stress hormones levels in the normal microenvironment may be predictive for chemically induced cancer in rats. Moreover, chemical carcinogenesis can promote stressor-like effects with hormonal changes in the tissue microenvironment, which may be associated to tumor progression.
Keywords: BDNF; Cancer; Carcinogenesis; Oral cancer; Stress hormones